2019
DOI: 10.3389/fpsyt.2019.00874
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Method Assessment of Sleep in Children With Angelman Syndrome: A Case–Controlled Study

Abstract: Objectives: To assess sleep quality and timing in children with Angelman syndrome (AS) with sleep problems using questionnaires and actigraphy and contrast sleep parameters to those of typically developing (TD) children matched for age and sex.Methods: Week-long actigraphy assessments were undertaken with children with AS (n = 20) with parent-reported sleep difficulties and compared with age and sex matched TD controls. The presence of severe sleep problems was assessed using the modified Simonds and Parraga s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 53 publications
0
16
0
2
Order By: Relevance
“…Conversely, new data on the sleep quality of this subgroup seem to strengthen the original finding that individuals with idiopathic ID experience poorer sleep quality than TD controls (Surtees et al 2018;Chan et al 2019). Further studies have also been published including people with ID and an associated genetic syndrome or neurodevelopmental condition, a number of which have suggested that original subgroup conclusions may not be congruous (Gunes et al 2019;Smith et al 2019;Trickett et al 2019).…”
Section: Introductionmentioning
confidence: 73%
“…Conversely, new data on the sleep quality of this subgroup seem to strengthen the original finding that individuals with idiopathic ID experience poorer sleep quality than TD controls (Surtees et al 2018;Chan et al 2019). Further studies have also been published including people with ID and an associated genetic syndrome or neurodevelopmental condition, a number of which have suggested that original subgroup conclusions may not be congruous (Gunes et al 2019;Smith et al 2019;Trickett et al 2019).…”
Section: Introductionmentioning
confidence: 73%
“…In addition to rare conditions which are linked to sleep disturbances such as Christianson Syndrome (Gruber et al, 2022), Dup15q Syndrome (Barstein et al, 2021), Pallister‐Killian Syndrome (Fetta et al, 2022), Phelan‐McDermid Syndrome and SYNGAP1‐ID (Smith‐Hicks et al, 2021), MBD5‐associated neurodevelopmental disorder (Gandhi et al, 2021), Arboleda‐Tham syndrome (Smith & Harris, 2021), Bosch‐Boonstra‐Schaaf optic atrophy syndrome (Rech et al, 2020) and emerging genetic variants including microdeletion syndrome at 2q22.1q22.3 and de novo DDX3X variants (Chen et al, 2020; Verhoeven et al, 2020). This shows that a wide array of specific intellectual disability syndromes are associated with sleep problems, although variation from night to night and within syndrome groupings is found (Trickett et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Для оценки сна у детей с СА использовался также метод актиграфии в течение 7 сут [36]. Не отмечено превышения по частоте пробуждений и значительного снижения длительности сна по сравнению с контрольной группой, имеются лишь статистически значимые расхождения во времени засыпания после выключения света.…”
Section: варианты расстройств сна у детей с синдромом ангельманаunclassified
“…С возрастом не отмечено значимой динамики изменения сна у детей с СА, в то время как в контрольной группе отмечается тенденция к засыпанию в более позднее время и укорочению длительности сна, что является отражением развития способности волевой депривации сна у здоровых детей для реализации собственных социальных нужд (подготовка к учебе, подъем по будильнику и т.д.) [36].…”
Section: о б з о р ы и л е к ц и и / R E V I E W S a N D L E C T U R E Sunclassified